2023
DOI: 10.1097/pas.0000000000002025
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Features in Congenital Pulmonary Airway Malformations and Pulmonary Sequestrations Correlate With Mutation Status

Abstract: Congenital pulmonary airway malformations (CPAMs) have a range of morphologies with varying cyst sizes and histologic features (types 1 to 3). Evidence suggested they arise secondary to bronchial atresia, however, we recently showed that cases with type 1 and 3 morphology are driven by mosaic KRAS mutations. We hypothesized that 2 distinct mechanisms account for most CPAMs: one subset is secondary to KRAS mosaicism and another is due to bronchial atresia. Cases with type 2 histology, similar to sequestrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Ongoing discoveries of the features that overlap between CPAM and other congenital lung lesions have raised controversy surrounding the Stocker classification system. Furthermore, a subset of CPAM harboring KRAS mutations is emerging as a distinctly different subtype, histologically and etiologically 72 …”
Section: Spectrum Of Neonatal Lung Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing discoveries of the features that overlap between CPAM and other congenital lung lesions have raised controversy surrounding the Stocker classification system. Furthermore, a subset of CPAM harboring KRAS mutations is emerging as a distinctly different subtype, histologically and etiologically 72 …”
Section: Spectrum Of Neonatal Lung Disordersmentioning
confidence: 99%
“…Furthermore, a subset of CPAM harboring KRAS mutations is emerging as a distinctly different subtype, histologically and etiologically. 72 CPAM may be first identified on prenatal screening ultrasound as heterogeneous hyperechoic masses with or without cysts. 65 In BA-CPAM, further characterization by fetal MRI typically demonstrates a corresponding lesion with T2 hyperintensity due to retained fluid, again with or without cysts depending on its type.…”
Section: Congenital Pulmonary Airway Malformation (Cpam)mentioning
confidence: 99%
“…KRAS mutations were found in all mucinous proliferation tissue, whereas the surrounding healthy lung tissue did not contain this mutation [ 24 26 ]. Specifically, KRAS mutations located on exon 2 G12V and G12D were found in both CPAM and mucinous AIS [ 17 , 25 , 27 31 ]. Because KRAS mutations found in lung tissue in adults supports the diagnosis of malignancy, we hypothesised that KRAS-positive CPAM patients ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital pulmonary airway malformations (CPAMs) are developmental anomalies of the lung that lead to respiratory complications and are rarely associated with adenocarcinoma ( 1 , 2 ). Stocker developed a classification system using cyst size and histology to distinguish five CPAM subtypes, CPAM Types 0–4, according to the affected tracheobronchial system segment ( 1 , 3 ). CPAM Type 0, now called acinar dysplasia, has a complex molecular pathogenesis with disruption of TBX4-FGF10 signaling playing a key role ( 1 , 2 ).…”
mentioning
confidence: 99%
“…The most distal lesion, pleuropulmonary blastoma (PPB) Type 1, formerly referred to as CPAM Type 4, is associated with germline DICER1 variants ( 2 , 4 ). The most common subtype, CPAM Type 1, is believed to originate from a major proximal bronchus and is characterized by large cysts and frequent mucinous cell clusters that may transform into mucinous adenocarcinoma ( 2 , 3 ). Recently, it was shown that CPAM Type 1 results from somatic KRAS mutations that are detected primarily in lesional mucinous and nonmucinous epithelial cells ( 5 ).…”
mentioning
confidence: 99%